Frontal plane tibio-femoral alignment and its association with knee pain among patients with early osteoarthritis of the knee in a population presenting to a tertiary hospital in South India - Koteshwar Rao, M.; Lakshmi Narayana Reddy, P. (International Journal of Research in Orthopaedics, 2017)
Background: Frontal plane knee malalignment may increase the progression of knee osteoarthritis (OA) and worsen functional capacity. Methods: In our study, the aim was to find the correlation of frontal plane tibiofemoral alignment with knee pain in early OA knee patients. After meeting the inclusion and exclusion criteria, 195 patients with 314 knees (104 females, 91 males) were studied. Clinical and radiological measurements of frontal plane tibiofemoral alignment, using landmark of hip, knee, and ankle, compared with knee pain. Results: The accepted Statistical significance was p<0.05. Patients with 130 knees (41%) were normal alignment, and 184 knees (59%) were abnormal alignment. The mean±SD age in our study was 54.6±8.9 years. The mean±SD BMI in our study to be 25.86±1.96. Mean±SD Q-angle in patients with normal and abnormal alignment was 14.76±1.54 and 14.63±1.9 respectively. There is statistically no significant correlation between BMI and VAS score (r=0.054, p=0.344). Means±SD of mLDFA, mMPTA, mTFA, aTFA, and JOA were 88.86±2.73, 84.96±3.00, 5.96±4.01, 4.55±3.67, and 2.37±1.88 respectively. JOA and mTFA had statistically significant weak positive correlation with VAS (knee pain) score, (r=0.281) (p=0.000) and (r=0.236) (p=0.000) respectively. The rest of the angles were not had statistically significant correlation with VAS score. The mTFA had statistically significant weak positive correlation with all the angles. We found that Frontal plane tibiofemoral alignment correlates with knee pain in patients with early OA. Conclusions: The mTFA may be considered one important criterion in designing treatment and planning surgery for patients with primary osteoarthritis. The Q angle acts as a good alternative clinical tool in assessing frontal plane alignment. BMI was not correlating with knee pain (VAS score).